Cost effectiveness and quality of life analysis of extracorporeal cardiopulmonary resuscitation (ECPR) for refractory cardiac arrest. (June 2019) - Dennis, Mark; Zmudzki, Fredrick; Burns, Brian; Scott, Sean; Gattas, David; Reynolds, Claire; Buscher, Hergen; Forrest, Paul; ,
Abstract: Background: The use of extracorporeal membrane oxygenation (ECMO) in refractory cardiac arrest (ECPR) has increased exponentially. ECPR is a resource intensive service and its cost effectiveness has yet to be demonstrated. We sought to complete a cost analysis with modelling of cost effectiveness and quality of life outcomes. We sought to complete a cost analysis with modelling of cost effectiveness and quality of life outcomes of patients who have undergone ECPR. Methods: Using data on all extracorporeal cardiopulmonary resuscitation (ECPR) patients at two ECMO centres in Sydney, Australia; we completed a costing analysis of ECPR patients. A Markov model of cost, quality of life and survival outcomes was developed to examine cost per QALY estimates and incremental cost effectiveness ratios (ICERs). Probabilistic sensitivity analysis (PSA) was completed to assess the probability of cost effectiveness for base case and variations. Results: Sixty-two consecutive ECPR patients were analysed; mean age of 51.9 ± 13.6 years, 38 (61%) were in hospital cardiac arrests (IHCA). Twenty-five patients (40%) survived to hospital discharge; all with a cerebral performance category (CPC) of 1 or 2. The mean cost per ECPR patient was AUD 75, 165 (€50, 535; ±AUD 75, 737). Over 10 years ECPR was estimated to add a mean gain of 3.0 Quality Adjusted Life Years (QALYs) per patient with an incremental cost effectiveness ratio (ICER) of AUD 25, 212 (€16, 890) per QALY, increasing to 4.0 QALYs and an ICER of AUD 18, 829 (€12, 614) over a 15-year survival scenario. Mean cost per QALY did not differ significantly by OHCA or IHCA. Conclusions: ECMO support for refractory cardiac arrests is cost effective and compares favourably to accepted cost effectiveness thresholds.